Vibration suppression using multi-impulse robust shaping method of zero vibration and derivative. (3rd February 2019) - Du, Yanfeng; Wang, Cong; Lu, Juncheng; Zhou, Yan
Abstract: A new multi-impulse robust shaper (MIR) is put forward to control the residual vibration of the flexible system actively in this paper. This technique designs a sequence of impulses according to the undamped natural frequency and the damping ratio of the flexible system to shape the input command. The input command shaped by MIR shaper can suppress the transient vibration and residual vibration and is robust to modeling errors in natural frequency and damping ratio of the flexible system to some extent. The shaped input command by MIR shaper can also suppress the high mode residual vibration under a certain level in a wide range of normalized frequency. The characteristic of the proposed MIR shaper is investigated in this paper, which shows a good advantage and broad application with comparison to the traditional ZV shaper, ZVD shaper and EI shapers.